In solving the equation (x + 4)(x – 7) = -24, Eric stated that the solution would be
x + 4 = -24 => x = -28
or
(x – 7) = -24 => x = -17
However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Yep, Eric messed up, he did not solve the problem.

\[(x+4)(x-7)=-24\]
\[x^2-3x-28=-24\]
\[x^2-3x-52=0\]
etc

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.